UMPSA organises Level 1 Swimming Coach and Water Rescue Programme - Siti Rabiatull Aisha, Idris (UMPSA, 2023)
SHAH ALAM, 25 September 2023 - The Faculty of Mechanical and Automotive Engineering Technology (FTKMA), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) in collaboration with Aquasplash Academy recently organised a Level 1 Swimming Coach and Water Rescue programme.